Research on the Development of Intelligent Financial Education in the Era of Artificial Intelligence - Liang, Tingting; Zhang, Hao (LPPM STIKI Malang, 2024)
With the continuous progress of the digital era, artificial intelligence is increasingly interwoven with various fields. This paper focuses on the current status of financial management courses, applies the SWOT analysis method to analyze the current situation of the development of financial education, proposes the problems existing in current courses, discusses the limitations of traditional teaching, explores the application of AI technology in financial management education, improves and refines course design, breaks the limitations of traditional teaching methods, emphasizes the integration of theory and practice, enhances students' professional competence, cultivates financial management thinking, and builds an intelligent teaching platform. On this basis, it discusses the specific applications of AI in three parts: designing basic courses, cultivating professional competence and thinking, and building a teaching platform. The aim is to innovate financial management education, promote its sustainable and innovative development, and cultivate high-quality talents who can meet the needs of the future financial industry.